Biomass valorization by thermal treatments: Graphene-based materials and their application on glyphosate adsorption - Hernández-Barreto, Diego Felipe; Bernal, Valentina; Giraldo, Liliana; Moreno-Piraján, Juan Carlos; Rodriguez-Estupiñán, Paola (Frontiers in Sustainability, 2022)
Carbon-based nanomaterials have exceptional physicochemical properties like high surface area and active sites, suitable for the adsorption of inorganic and organic compounds. Currently, these materials are being tested for environmental applications, e.g., detection of emerging pollutants in drinking and surface water. In this work, different methods to prepare graphene (G) or graphene-based materials (GBM) using biomass, or its constituents are reviewed. This text brings together the methods used to revalue biomass by converting it into graphene materials from thermal treatments and their application on the adsorption of glyphosate from aqueous solution. Computational studies were also added to evaluate the information about interactions between the herbicide and graphene layers